A typology of creative cities in the world: lessons learned - Rato, B. (2012)
We propose as a tool a typology of different types of approaches aiming at the development of creative industries and their specific challenges, characteristics which can lead to failure and recommendations. In this way, policy-makers can easily identify their strategy with a particular approach and to look in detail at the key-questions resulting from the experience of other cities. The definition of our typology is the result of the analysis of several case studies (not extensively mentioned in the paper), based on desk-top research and on interviews for the our research project (project CreatCity - "A governance culture for the creative city: urban vitality and international networks", conducted by Dinâmia (Research Centre on Socioeconomic Change of the ISCTE/Lisbon) and financed by Fundação para a Ciência e a Tecnologia/Ministério da Ciência, Tecnologia e Ensino Superior, with the support of ERDF and national funds of the MCTES (Refª. Proj. PTDC/AUR/65885/2006).